Public Figures and Social Media from a Freedom of Expression Viewpoint in the Recent U.S. and EU Jurisdiction - Gergely Gosztonyi; János Bálint; Gergely Ferenc Lendvai (Journalism and Media)
Social media has transformed political communication’s landscape, reshaping how politicians engage with the public and express their views. The tension between freedom of expression and the need for responsible governance and politicians became more visible. This article examines the nuances of politicians’ freedom of expression on social media, emphasizing the importance of the right to receive information and participate in public debate. Furthermore, it explores the idea of social media profiles as public forums, examines the level of protection afforded to public officials in public discourse, and compares the content moderation frameworks in the United States and the European Union.